Mirjiam Fried, Jan-Ola Östman y Jef Verschueren (Eds.) Variation and Change. Pragmatic perspectives - Araya, Milena; Hasler, Felipe (Lenguas Modernas, 2011)
Amsterdam/Filadelfia: John Benjamins Publishing Company. 2010, 275 páginas